EARNINGS MANAGEMENT FOR BONUS COMPENSATION - Isyrohil Muyassaroh; Imam Subekti; Zaki Baridwan (Faculty of Economics and Business, University of Pasundan, 2021)
The objectives of this quantitative study are to investigate the practice of earnings management which is proxied by Loan Loss Provision and Loan Loss Allowance and to assess the effect of bonuses on earnings management practices. Using purposive sampling, 102 banks were selected as the sample. The assessment includes one-sample t test and linear regression test. This study finds that banks commit earnings management practices by reducing LLA values and that bonuses negatively influence the practice of earnings management as proxied by LLP.